PENGARUH BRAND IMAGE DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN SHAMPOO MEREK PANTENE (Studi pada Mahasiswi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Diponegoro) - Fairuz Amalia; Sudharto Prawoto Hadi (Jurnal Ilmu Administrasi Bisnis, 2017)
Shampoo is one of the treatment products that has functioned as hair treatment and has become a daily necessity for everyone. Pantene always place at top of the survey published by SWA Magazine in 2013-2015. However the percentage of brand value and brand share showed declined. This is indicated by the declined in brand value, from 2013 to 2014 is decreased by 0.6% and 2014 to 2015 decreased by 14.7%, as well brand share also declined at 2.4% from 2013 to 2014 and 2014 to 2015 decreased by 0.6%,This research is aiming at revealing the influence of brand image and celebrity endorser on Pantene brand purchasing decision of the students of Faculty of Social and Political Sciences, Diponegoro University. The type of research is explanatory research and the number of sample taken is 100 students purchasing and using Pantene shampoo. The sampling technique are accidental sampling and purposive sampling. The data collection techniques are questionnaire and observation. The data analysis technique is a correlation test data analysis, determination test, simple linear regression test, multiple linear regression test, t test and f test using IBM SPSS (Statistical Product and Service Solutions) program version 16.0.The result of this study are positive correlation between brand image and celebrity endorser to purchasing decision partially and simultaneously. Based on the results of the regression analysis, it is known that the variable brand image and celebrity endorser influence on purchasing decision with a coefficient of 0,480 and 0,289. Therefore it can be advised that Pantene has to strongly strengthen their brand image and carefully reevaluate their celebrity endorser in Pantene advertisement.